(untitled) (American AgriTech: Journal of Agricultural Technology Innovation and Sustainability, 2026)
Currently, the control of annual and perennial cereal weeds, as well as some annual and biennial weeds that negatively affect the growth and development of polydora plants, is relevant. This article provides information on determining the biological efficacy of Escudo 50% w/v on tomato plants